2022
DOI: 10.1097/jcma.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological and genetic differences among gastric cancer patients with no recurrence, early recurrence and late recurrence after curative surgery

Abstract: Background: To date, few reports have investigated the genetic alterations and clinicopathological features among gastric cancer (GC) patients with no tumor recurrence, early recurrence, and late recurrence following curative surgery. Methods: A total of 473 GC patients undergoing curative surgery were included. The clinicopathological characteristics, patient prognosis, recurrence patterns, and genetic alterations were compared between GC patients with early recurrence and late recurrence.Results: Among the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…The article published in the January issue of the Journal of the Chinese Medical Association entitled "The clinicopathological and genetic differences among gastric cancer patients with no recurrence, early recurrence, and late recurrence after curative surgery" attempted to explore this topic, since the authors' enrolled subjects belonged to complete resection of tumors and all of them received the curable surgery claimed by authors. 12 The authors enrolled 473 patients with gastric cancer (GC) undergoing curative surgery to investigated the impact of genetic alterations and clinicopathological features on disease-free survival (DFS) and overall survival (OS) in these GC patients. 12 DFS was classified as no recurrence, early recurrence (defined by < 2 years) and late recurrence (defined by ≥ 2 years).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The article published in the January issue of the Journal of the Chinese Medical Association entitled "The clinicopathological and genetic differences among gastric cancer patients with no recurrence, early recurrence, and late recurrence after curative surgery" attempted to explore this topic, since the authors' enrolled subjects belonged to complete resection of tumors and all of them received the curable surgery claimed by authors. 12 The authors enrolled 473 patients with gastric cancer (GC) undergoing curative surgery to investigated the impact of genetic alterations and clinicopathological features on disease-free survival (DFS) and overall survival (OS) in these GC patients. 12 DFS was classified as no recurrence, early recurrence (defined by < 2 years) and late recurrence (defined by ≥ 2 years).…”
mentioning
confidence: 99%
“…None of evaluated molecular pathological parameters, such as microsatellite instability (MSI), Helicobacter pylori (HP), Epstein-Bar virus (EBV), and genetical mutations (PI3K/AKT pathway, TP53, ARID1A, and B-Raf proto-oncogene [BRAF]) were useful in the prediction of DFS and OS, and by contrast, only conventional clinicopathological parameters, such as elder population (≥ 65 years), and pathological N (lymph node) category were involved in the OS. 12 Therefore, subgroup analysis was conducted and finally, the authors found the potential role of PIK3CA amplifications and ARID1A mutations may be related to the certain-type outcomes, such as early recurrence as well as single-site recurrence, respectively. 12 Recently, technological improvement, the better understanding of tumorigenesis, the continuous innovation of targeted therapy and chemotherapy regimens, the spread of advanced development of surgery and multidisciplinary decision-making have directed patient-tailored strategies, with the aim of improvement of DFS and OS.…”
mentioning
confidence: 99%
See 3 more Smart Citations